Equivalence and Bifurcations of Finite Order Stochastic Processes - Cees Diks; Florian Wagener (Tinbergen Institute, 2005)
This article presents an equivalence notion of finite order stochastic processes. Local dependence measures are defined in terms of joint and marginal densities. The dependence measures are classified topologically using level sets. The corresponding bifurcation theory is illustrated with some simple examples.
Keywords: C14; 330; Stochastic processes; structural stability; copula density; bifurcations; Stochastischer Prozess; Nichtparametrisches Verfahren; Theorie